PSYCHOLOGY OF LIFE-SENSE EMOTIONAL EXPERIENCE OF MODERN STUDENT YOUTH - Halian, Ihor; Halian Оlena (PSYCHOLOGICAL JOURNAL, 2018)
The article presents the results of theoretical and empirical study of the depth of the life-sense emotional experience of youth in modern transformational society. Agent’s subjective experience of the integrity and meaningfulness of one’s own being is denoted by the term “psychological well-being”. It is pointed to its integrative essence which expresses the degree of a person’s orientation to the implementation of personality growth, self-acceptance, life goals, positive relationships with the environment, as well as the degree of realization of this orientation expressed through the feeling of happiness and satisfaction both with yourself and your own life. It is noted that the fundamental values ​​for psychological well-being are fulfilled personality values, whose structure is invariant under different conditions. It is stated that it is life goals that have the potential to stimulate a person to specific actions that will give sense to life. There has been proved the possibility of diagnostics of value-sense formations. On the one hand, sense of life is rarely directly objectified in behaviour, and therefore, judging by the actions of the personality in a particular situation we can state only the “final links” of the mechanism of life-sense regulation. On the other hand, regulatory structures and processes objectified in actions are “derivatives” of life sense, available for empirical registration. It is shown that the choice of certain values ​​as sources of life sense substantially determines the general level of life awareness and personal vulnerability to life-sense crises. The key factor in the emergence of a life-sense crisis is the inadequate depth of life awareness. The obtained empirical results have shown a not too high level of existential fulfilment of young people. However, they have not been diagnosed with crisis of life sense. Insufficiently high indicators of depth of life sense indicate a qualitatively peculiar picture of their internal emotional experiences together with low existential fulfilment as to their own lives. The emphasis is placed on the optimality of the spiritual life sense, for which self-transcendental values ​​are fundamental. There has been confirmed the influence of psychological well-being (existential fulfilment) on the manifestation of a high level of psychological activity.